2000
DOI: 10.1021/jp002635q
|View full text |Cite
|
Sign up to set email alerts
|

On the Coverage-Dependent Adsorption Geometry of Benzene Adsorbed on Pd{111}: A Study by Fast XPS and NEXAFS

Abstract: Fast XPS data obtained during benzene uptake on Pd{111} are consistent with those obtained during benzene desorption, and both are in accord with the corresponding NEXAFS results. At low coverage the molecule lies flat, is strongly adsorbed, and is characterized by a relatively low C 1s binding energy. At higher coverage, a second form of benzene is also present. This species is strongly tilted with respect to the metal surface. It is characterized by a relatively high C 1s binding energy and a narrower π* res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 25 publications
7
52
1
Order By: Relevance
“…Meanwhile, the band intensities due to aromatic ring structure (1610, 1587, 1489 and 1465 cm À1 ) increased, which denoted some species with an aromatic ring structure was still existed on the catalyst surface at this temperature. The orientation change of the adsorbed ring structure from parallel to tilt (vertical) [16,35,36] and/or more molecules with an aromatic ring structure adsorbed on the catalyst could contribute to the increase of intensity. Based on the results, we can conclude that the phthalate species was formed at this reaction temperature.…”
Section: Catalytic Reaction Mechanismmentioning
confidence: 99%
“…Meanwhile, the band intensities due to aromatic ring structure (1610, 1587, 1489 and 1465 cm À1 ) increased, which denoted some species with an aromatic ring structure was still existed on the catalyst surface at this temperature. The orientation change of the adsorbed ring structure from parallel to tilt (vertical) [16,35,36] and/or more molecules with an aromatic ring structure adsorbed on the catalyst could contribute to the increase of intensity. Based on the results, we can conclude that the phthalate species was formed at this reaction temperature.…”
Section: Catalytic Reaction Mechanismmentioning
confidence: 99%
“…Adsorption of benzene on Pd (1 1 1) has been examined extensively with various surface science techniques, such as low-energy electron diffraction (LEED) [11,12], near-edge X-ray absorption fine structure (NEXAFS) [13,14], ultraviolet photoelectron spectroscopy [13], X-ray photoelectron spectroscopy [13,14], and temperature-programmed desorption (TPD) [15]. These studies reveals that, at low coverages, benzene is adsorbed lying parallel through the interaction of electrons with the surface, and that, at higher coverages, benzene is adsorbed in a tilted geometry.…”
Section: Adsorption Energies and Structures Of Benzenementioning
confidence: 99%
“…The threshold coverage for the transition from flat to tilted benzene molecules has been estimated from combined TPD and molecular beam measurements to be H % 0:13 ML and by XPS investigations to be H % 0:16 ML [12,22]. In contradiction to these findings, HREELS investigations by Waddill et al demonstrated the existence of only one adsorbed configuration with the ring plane parallel to the surface even for adsorption temperatures as low as 150 K [13].…”
Section: Introductionmentioning
confidence: 98%
“…For adsorption temperatures below 300 K and higher coverages, a tilted benzene configuration was inferred from a simulation of TPD spectra and directly derived from NEXAFS data [12,21,22]. The threshold coverage for the transition from flat to tilted benzene molecules has been estimated from combined TPD and molecular beam measurements to be H % 0:13 ML and by XPS investigations to be H % 0:16 ML [12,22].…”
Section: Introductionmentioning
confidence: 99%